Diagnóstico financiero y administración del capital de trabajo en la empresa Triple C Import’s de la ciudad de Loja, periodos 2013 y 2014 - Castro Robles, Raquel Noemí (2017)
The thesis work entitled “DIAGNÓSTICO FINANCIERO Y ADMINISTRACIÓN DEL CAPITAL DE TRABAJO EN LA EMPRESA TRIPLE C IMPORT’S DE LA CIUDAD DE LOJA, PERIODOS 2013 Y 2014”, was held in order to analyze the real economic situation of the company, for this work can contribute in making appropriate financial decisions by the manager and serve to improve their financial situation. The financial structure of the company's Triple C Import analyzed through the implementation of horizontal and vertical analysis, in addition to the application of indicators of liquidity management, debt and profitability. A comprehensive working capital analysis using formulas that allowed us to know their proportionality and variation within the periods studied was made. Finally with all the information obtained could produce the report of the Financial Diagnosis and Management of Working Capital, which comprise the results obtained and with which it was determined that the company during its existence has not carried out a financial analysis , accounts receivable are not handled by proper credit policy which makes them doubtful accounts. It is recommended that the policy meets payment of 45 days.